The Effects of Jigsaw and GTM on the Reading Comprehension Achievement of the Second Grade of Senior High School Students - Yullia Rossiana (Widya Mandala Surabaya Catholic University, 2010)
The aim of this study is to compare the effectiveness of Jigsaw and GTM on second grade of senior high school students’ reading achievement. The subjects of the study used are two classes of the second grade of St. Agnes Senior High School. A quasi-experimental research with a pretest-posttest non-equivalent control group design was used to do this research. In order to know the effects of those two techniques, the writer used the pretest posttest as the instrument with 16 multiple choice items. To calculate the data, t-test for significance of difference between two means for independent samples was used. After analyzing the data which had been collected, the writer found out that the mean of the gain scores of the experimental group was 1.68 and the control group was 0.81. The mean of the gain scores between the two groups were not significantly different. It means the students who were taught using Jigsaw technique did not have a better reading achievement than those who were taught using GTM. Introduction